Penerapan Media Pembelajaran Berbasis Kahoot pada Mata Pelajaran Dasar-Dasar Ketenagalistrikan - Ahmad Fabian; Doni Tri Putra Yanto (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2026)
This study aims to analyze the effect of implementing Kahoot-based learning media on student learning outcomes in the Basic Electrical Engineering course for Grade X Electrical Power Installation Engineering (TITL) students at SMKN 2 Sungai Penuh. A quantitative approach with a quasi-experimental design—specifically, a pretest-posttest control group design—was employed. The research involved two groups: an experimental class (N = 15) that received interactive Kahoot-based instruction, and a control class (N = 20) that followed conventional teaching methods. Data were collected using multiple-choice learning achievement tests administered before (pretest) and after (posttest) the intervention. Data analysis included descriptive statistics and inferential tests, namely the normality test, the homogeneity test, and the independent samples t-test. Results showed a significant increase in the experimental group’s posttest mean score (70.2) compared to the control group (38.5). The hypothesis test yielded a significance value of 0.000 (< 0.05), indicating a statistically significant positive effect of Kahoot on student learning outcomes. These findings suggest that Kahoot is an effective interactive learning medium for enhancing students’ conceptual understanding of electrical engineering fundamentals in vocational education settings.